Comparison of long-term cardiovascular and renal outcomes between percutaneous coronary intervention and coronary artery bypass grafting in multi-vessel disease with chronic kidney disease - Woochan Kwon; Ki Hong Choi; Dong Seop Jeong; Sang Yoon Lee; Joo Myung Lee; Taek Kyu Park; Jeong Hoon Yang; Joo-Yong Hahn; Seung-Hyuk Choi; Su Ryeun Chung; Yang Hyun Cho; Kiick Sung; et al. (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveThis study aims to analyze cardiac and renal outcomes of chronic kidney disease (CKD) patients with multi-vessel disease who have undergone coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI).Materials and methodsChronic kidney disease patients with multi-vessel disease who underwent CABG or PCI were retrospectively selected from our database and divided into the PCI group [further stratified into PCI with complete revascularization (PCI-CR) and PCI with incomplete revascularization (PCI-IR) groups] and the CABG group. The primary endpoint was the composite of all-cause death, myocardial infarction (MI), or stroke at 5 years. The key secondary endpoint was the 5-year rate of the renal composite outcome, defined as >40% glomerular filtration rate decrease, initiation of dialysis, and/or kidney transplant. Outcomes were compared using Cox proportional hazards regression analysis, and the results were further adjusted by multivariable analyses and inverse probability weighting.ResultsAmong the study population (n = 798), 443 (55.5%) patients received CABG and 355 (44.5%) patients received PCI. Compared with the CABG group, the PCI group had similar risk of the primary endpoint (CABG vs. PCI, 19.3% vs. 24.0%, HR: 1.28, 95% CI: 0.95–1.73, p = 0.11) and a lower risk of the renal composite outcome (36.6% vs. 31.2%, HR: 0.74, 95% CI 0.58–0.94, p = 0.03). In addition, PCI-IR was associated with a significantly higher risk of the primary endpoint than CABG (HR: 1.54, 95% CI: 1.11–2.13, p = 0.009) or PCI-CR (HR: 1.78, 95% CI: 1.09–2.89, p = 0.02). However, PCI-CR had a comparable 5-year death, MI, or stroke rate to CABG (HR: 0.86, 95% CI 0.54–1.38, p = 0.54).ConclusionCoronary artery bypass grafting showed an incidence of death, MI, or stroke similar to PCI but was associated with a higher risk of renal injury. PCI-CR had a prognosis comparable with that of CABG, while PCI-IR had worse prognosis. If PCI is chosen for revascularization in patients with CKD, achieving CR should be attempted to ensure favorable outcomes.Clinical trial registration[clinicaltrials.gov], identifier [NCT 03870815].